Role of CrRLK1L Cell Wall Sensors HERCULES1 and 2, THESEUS1, and FERONIA in Growth Adaptation Triggered by Heavy Metals and Trace Elements - Richter, Julia; Ploderer, Marie; Mongelard, Gaëlle; Gutierrez, Laurent; Hauser, Marie-Theres (Frontiers in Plant Science, 2017)
Cell walls are not only a protective barrier surrounding protoplasts but serve as signaling platform between the extracellular environment and the intracellular physiology. Ions of heavy metals and trace elements, summarized to metal ions, bind to cell wall components, trigger their modification and provoke growth responses. To examine if metal ions trigger cell wall sensing receptor like kinases (RLKs) of the Catharanthus roseus RLK1-like (CrRLK1L) family we employed a molecular genetic approach. Quantitative transcription analyses show that HERCULES1 (HERK1), THESEUS1 (THE1), and FERONIA (FER) were differently regulated by cadmium (Cd), nickel (Ni), and lead (Pb). Growth responses were quantified for roots and etiolated hypocotyls of related mutants and overexpressors on Cd, copper (Cu), Ni, Pb, and zinc (Zn) and revealed a complex pattern of gene specific, overlapping and antagonistic responses. Root growth was often inversely affected to hypocotyl elongation. For example, both HERK genes seem to negatively regulate hypocotyl elongation upon Cd, Ni, Zn, and Pb while they support root growth on Cd, Cu, and Ni. The different THE1 alleles exhibited a similar effect between roots and hypocotyls on Ni, where the loss-of-function mutant was more tolerant while the gain of function mutants were hypersensitive indicating that THE1 is mediating Ni specific inhibition of hypocotyl elongation in the dark. In contrast hypocotyl elongation of the knock-out mutant, fer-4, was hypersensitive to Ni but exhibited a higher tolerance to Cd, Cu, Pb, and Zn. These data indicate an antagonistic action between THE1 and FER in relation to hypocotyl elongation upon excess of Ni. FERs function as receptor for rapid alkalinization factors (RALFs) was tested with the indicator bromocresol purple. While fer-4 roots strongly acidified control and metal ion containing media, the etiolated hypocotyls alkalized the media which is consistent with the already shorter hypocotyl of fer-4. No other CrRLK1L mutant exhibited this phenotype except of the THE1:GFP overexpressor on Ni suggesting that THE1 might be involved in Ni induced and hypocotyl specific RALF signaling and growth regulating pathway. Overall, our findings establish a molecular link between metal ion stress, growth and the cell wall integrity sensors of the CrRLK1L family.